Ecological Analysis of Diabetes Mellitusin Indonesia - Oskar Renagalih Amarta; Djazuly Chalidyanto; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Diabetes mellitus is a dangerous disease and often causes complications. The study aims to analyzeecologically the factors related to the prevalence of Diabetes Mellitus in Indonesia. The study was designedwith an ecological analysis approach, using secondary data from the 2018 Indonesia Basic Health Surveycovering all provinces as samples. The dependent variable is the prevalence of diabetes mellitus. Theindependent variable is the prevalence of obesity nutritional status according to BMI in the adult population(aged >18 years), the proportion of less physical activity in the population aged >10years, the proportion ofsweet drink consumption habits in the population >3 years old more than once per day and the percentage ofpoor people. Data were analyzed using the scatter plot.The results showed that the higher the prevalence ofobesity nutritional status according to BMI in the adult population, the higher the proportion of less physicalactivity, and the higher the proportion of sweet drink consumption habits in the population more than onceper day, the higher the prevalence of diabetes mellitus. Conversely, the higher the percentage of poor people,the lower the prevalence of diabetes mellitus. The study concluded that the four independent variables testedtend to relate to the prevalence of diabetes mellitus.